RETRACTED: Prospects for the transformation of video game media rhetoric in terms of the influence of artificial intelligence - Tarasov Aleksey; Belyaev Dmitry (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001